Coprolites in a Middle Triassic cycad pollen cone: evidence for insect pollination in early cycads? - Klavins, Sharon D.; Kellogg, Derek W.; Krings, Michael; Taylor, Edith L.; Taylor, Thomas N. (Evolutionary Ecology, 2015)
This is the publisher's version, also available electronically from http://www.evolutionary-ecology.com/issues/v07n03/kkar1828.pdf. Question: What evidence is there for cycad–insect interactions in the fossil record? Organism: The pollen cone Delemaya spinulosa Klavins, Taylor, Krings et Taylor. Locality: Fremouw Formation (Middle Triassic), Fremouw Peak, Central Transantarctic Mountains, Antarctica. Methods: We document the presence of pollen-laden coprolites in pollen sacs of a Middle Triassic cycad. Conclusions: These coprolites are comparable with fecal pellets of modern arthropods and we suggest that they were produced by beetles. This provides the oldest unequivocal evidence for a cycad–insect interaction and may represent a precursory stage in the establishment of a more complex cycad–pollinator relationship.